2014
DOI: 10.1007/s00586-014-3502-9
|View full text |Cite
|
Sign up to set email alerts
|

Screw perforation features in 129 consecutive patients performed computer-guided cervical pedicle screw insertion

Abstract: Careful insertion of pedicle screws is necessary, especially at C3 to C5, even when using a CT-based navigation system. Pedicle screws tend to be laterally perforated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 18 publications
2
29
0
Order By: Relevance
“…But not all the results about using the navigation in CPSs placement were optimistic. Uehara et al (15)inserted the CPSs by using a CT-based navigation system during operations. The results showed that the combined rate of grades 2 and 3 perforations was 20.0 % (116/579).…”
Section: Discussionmentioning
confidence: 99%
“…But not all the results about using the navigation in CPSs placement were optimistic. Uehara et al (15)inserted the CPSs by using a CT-based navigation system during operations. The results showed that the combined rate of grades 2 and 3 perforations was 20.0 % (116/579).…”
Section: Discussionmentioning
confidence: 99%
“…Several reports have described the efficacy of intraoperative 3D navigation systems to aid in the placement of cervical pedicle screws [2123]. A clinical study by Richter et al [21] noted that the prevalence of pedicle perforations was 8.6% in a conventional treatment group and 3.0% in a 3D navigation group.…”
Section: Discussionmentioning
confidence: 99%
“…In their study, 9 pedicle screw breaches were encountered with no vertebral artery injury, as the vertebral artery does not occupy the complete foramen transversarium and mild breach would not usually cause complications. On the contrary, Uehara et al reported that a perforation of more than 50% of the screw diameter in the preoperative CT navigation procedure was observed at the highest frequency at C4 and at the lowest frequency at C3 and C6 71) .…”
Section: Surgery-related Complicationsmentioning
confidence: 94%
“…Pedicle Breach and Complications Yukawa et al 75 (X rays -oblique views) NCB: 10.3% CB: 4% Neo et al 51 (Abumi technique) C: 25% Kotani et al 65 Free hand C: 6.7% CAS C: 1.2% Karaikovic et al 57 NCB: 9.7% (Funnel technique) CB: 7.1% Ludwig et al 53 Surface landmarks NCB: 21.9%, CB: 65.5% Laminoforaminotomy NCB: 15.4%, CB: 39.6% CAS NCB: 13.4%, CB: 10.6% Richter et al 67 Conventional C: 8.6% CAS C: 3% Yoshimoto et al 78 NCB: 7.3% CB: 3.7% Ito et al 79 C: 2.8% (CAS) Ishikawa et al 66 Conventional C: 27% CAS C: 18.7% Nakashima et al 73 C: 5.9% Uehara et al 71 NCB: 20.0%, CB: 6.7% NCB, non-critical breach; CB, critical breach; C, complications…”
Section: Authorsmentioning
confidence: 99%